A Literature Review of ERP Implementation in African Countries. Issue 1 (5th December 2017) - Tobie, Armand Manga; Etoundi, Roger Atsa; Zoa, Jean
Abstract: This paper is a literature review of articles published in various journals and conference proceedings, dealing with the topic of the implementation of Enterprise Resource Planning (ERP) within African countries. It intends to help researchers interested in the topic by showing the problems that have been addressed in the research. This work also highlights open issues that can be tackled in future research in the development of African countries driven by ERP. Conferences and journals that are interested in the implementation of ERP within African countries have been identified. The paper also discusses whether the implementation of ERP is an important topic or a market place in the African continent. Based on the salient information gathered throughout this paper review, this work draws some recommendations that will contribute to the successful implementation of ERP within African countries. These recommendations go from the awareness of existing problems and solutions, the life cycle used in the implementation of ERP, to the successful implementation of ERP by avoiding failures that are linked to the African context.